Enhancement of role modelling in clinical educators: A randomized controlled trial. (2nd April 2020) - Mohammadi, Elaheh; Mirzazadeh, Azim; Sohrabpour, Amir Ali; Shahsavari, Hooman; Yaseri, Mehdi; Mortaz Hejri, Sara
Abstract: Introduction: Role models have an important impact on the professional behavior of medical students. Previous investigations help us understand how to improve role modelling. However, studies aiming at enhancing role modelling among clinical educators are very limited and generally lack comprehensive evaluations of the designed programs. We intended to gather robust evidence on the effectiveness of a longitudinal program for enhancing role modelling. Methods: Clinical educators were divided into intervention and control groups. The longitudinal program, developed based on the exposure phase of the 'Positive Doctor Role Modelling' framework, was delivered during three months of onsite and online sessions. The effectiveness of the program was assessed in three levels of reaction, learning, and behavior. Results: In the intervention group ( N  = 18), the mean score of satisfaction was 4.7 ( SD  = 0.5), and the learning (awareness about role modelling) improved significantly after the program (3.33–4.34), comparing to the control group (3.53–3.63). There was no significant difference in terms of behavior improvement between the two groups, before and after the program. Conclusions: Our findings indicate that our longitudinal faculty development program on role modelling was highly appreciated by clinical educators, and improved their awareness and deliberate role modelling.